CTNI-67. EFFICACY AND SAFETY OF LAROTRECTINIB IN PATIENTS WITH TROPOMYOSIN RECEPTOR KINASE (TRK) FUSION PRIMARY CENTRAL NERVOUS SYSTEM (CNS) TUMORS: AN EXPANDED DATASET. (9th November 2020) - Perreault, Sébastien; Doz, François; Drilon, Alexander; Geoerger, Birgit; Boni, Valentina; Chisholm, Julia; Dubois, Steven G; Grilley-Olson, Juneko E; Hong, David S; Italiano, Antoine; Kang, HyoungJin; Nysom, Karsten; et al.
Abstract: BACKGROUND: TRK fusion proteins are oncogenic drivers of various CNS and non-CNS tumors. Larotrectinib, a highly selective FDA- and EMA-approved TRK inhibitor, demonstrated an objective response rate (ORR) of 79% across various non-CNS cancers (Hong et al. Lancet Oncol. 2020). We report data in an expanded set of TRK fusion primary CNS tumors treated with larotrectinib. METHODS: Patients with primary CNS tumors harboring an NTRK gene fusion treated with larotrectinib in two clinical trials (NCT02637687, NCT02576431) were identified. Disease status was investigator-assessed (RANO). Data cutoff: July 15, 2019. RESULTS: Twenty-four patients with TRK fusion primary CNS tumors were identified. Eighteen patients had gliomas (13 high-grade and five low-grade). Median age was 8.0 years (range 1.3–79.0), with 20 patients < 18 years old. ORR was 29% (95% CI 13–51%); best responses were two complete responses, five partial responses (two pending confirmation), 15 stable disease, and two progressive disease. The 24-week disease control rate was 63% (95% CI 41–81%). For the five confirmed responders, median time to best response was 1.8 months and median duration of response was 4.9 months (range 1.7+ to 10.1+). Median progression-free survival was 11.0 months (range 1.1 to 19.8+) and median overall survival was not reached (range 1.9+ to 21.4+) at a median follow-up of 6.0 months. Treatment duration ranged from 1.2 to 21.4+ months; three patients continued treatment beyond progression. Treatment-emergent adverse events (TEAEs) were mainly Grade 1 and 2. Grade 3–4 TEAEs occurred in 10 patients, with two deemed related to larotrectinib. The most common neurological TEAE was headache in three patients (Grade 1–2). No patients discontinued larotrectinib due to AEs. CONCLUSIONS: Larotrectinib was active and well tolerated in patients with TRK fusion primary CNS tumors. These results support testing for NTRK gene fusions in patients with primary CNS tumors.